GSK3 acts as a switch for transcriptional programs in a model of low-grade gliomagenesis - Marilin S Koch; Minh Deo; Lena-Marie Schmitt; Michael S Hoetker; Şevin Turcan (Acta Neuropathologica Communications)
Abstract Mutations in isocitrate dehydrogenase (IDH)1/2 are defining drivers of low-grade gliomagenesis. However, mutant IDH alone is not sufficient for malignant transformation, and additional events are required for the development of low-grade glioma. While specific genetic lesions have been identified to contribute to low-grade gliomagenesis, less is known about the signaling pathways involved in the acquisition of malignancy. To identify prerequisites of IDH mutant tumorigenesis, we modulated pathways previously implicated in glioma initiation using a tractable in vitro model system for early IDH1R132H-dependent gliomagenesis. Through the use of chemical compounds, we targeted WNT/GSK3, TGF-β and NOTCH-signaling, assessing their functional, transcriptional, and translational impacts. Expression of LGG-related marker L1CAM was affected by perturbation of all pathways, though only modulation of WNT/GSK3-signaling resulted in profound molecular transformation, including glioma-associated genes and programs regulating cellular architecture and cell replication. This was accompanied by altered cell morphology, migration capacity, and enhanced proliferation. Transcription factor RUNX2 was identified as a potential downstream effector, whose inhibition abrogated cell proliferation. Disrupted WNT/GSK3 signaling in a model system of early low-grade gliomagenesis fundamentally impacted cell fate, as demonstrated by a reshaped transcriptional landscape, aberrant transcription factor activity, extracellular matrix restructuring, and altered proliferation capacity. Our data suggests that GSK3 may play a central role during low-grade gliomagenesis, warranting further investigation.